Women’s Life in Indonesian Contemporary Short Stories: A Study of Ecofeminism Transformative - Aji Septiaji; Zuriyati Zuriyati; Aceng Rahmat (Jurusan Tadris Bahasa Indonesia, 2020)
Different characteristics between men and women in solving problems in their life become the background of this study. Men are guided by logic in solving the problems. On the other hand, women are guided by feelings, rely on communication, or have a communicative attitude to get other people's responses and find solutions through actions that can decrease hurt feelings. The study aims are to investigate the lives of women from various cases such as discrimination, natural exploitation, and gender stereotypes.The objects of this study are Indonesian contemporary short stories published in Kompas from 2010 until 2015. The technique of collecting data through selective stages includes data reduction, data presentation, and conclusion or verification. Dealing with a large number of data sources, only the most adequate and relevant data are analyzed. The results of this study indicate that women in the stories not only tell about the role of women in general but also emphasizes morality. Women as the characters who are categorized as gentle, loving, and caring can be antagonistic figures caused by the treatment of others (men). Meanwhile, denial from women as a form of resistance to something that dangerous to express what has become the right.Penelitian ini dilatarbelakangi bahwa perempuan memiliki karakteristik yang berbeda dengan laki-laki dalam menghadapi berbagai problematika kehidupan. Laki-laki dipandu oleh logika dalam memecahkan persoalan. Sementara itu, perempuan lebih dipandu oleh perasaan, mengandalkan komunikasi atau memiliki sikap komunikatif untuk memperoleh respons orang lain. Tujuan penelitian ialah mengungkap kehidupan perempuan-perempuan dari berbagai kasus seperti diskriminasi, eksploitasi alam, dan stereotip gender. Objek penelitian ialah cerpen-cerpen kontemporer Indonesia Kompas kurun waktu 2010-2015. Teknik pengumpulan data, meliputi: reduksi data, penyajian data, dan penarikan simpulan atau verifikasi. Hasil penelitian menunjukkan bahwa perempuan dalam cerita tidak hanya menceritakan tentang peran perempuan pada umumnya, tetapi juga menekankan moralitas. Perempuan sebagai karakter yang dikategorikan lembut, penuh kasih, dan peduli bisa menjadi tokoh antagonis yang disebabkan oleh perlakuan orang lain (laki-laki). Sementara itu, penyangkalan dari perempuan sebagai bentuk perlawanan terhadap sesuatu yang berbahaya untuk mengekspresikan apa yang telah menjadi haknya.